Contralateral eye-to-eye comparison of intravitreal ranibizumab and a sustained-release dexamethasone intravitreal implant in recalcitrant diabetic macular edema - Thomas BJ (Clinical Ophthalmology, 2016)
Benjamin J Thomas, Yoshihiro Yonekawa, Jeremy D Wolfe, Tarek S Hassan Department of Vitreoretinal Surgery, William Beaumont Hospital, Royal Oak, MI, USA Objective: To compare the effects of intravitreal ranibizumab (RZB) or dexamethasone (DEX) intravitreal implant in cases of recalcitrant diabetic macular edema (DME).Methods: Retrospective, interventional study examining patients with symmetric bilateral, center-involved DME recalcitrant to treatment with RZB, who received DEX in one eye while the contralateral eye continued to receive RZB every 4–5 weeks for a study period of 3 months.Results: Eleven patients (22 eyes) were included: mean logarithm of the minimal angle of resolution (logMAR) visual acuity (VA) for the DEX arm improved from 0.415 (standard deviation [SD] ±0.16) to 0.261 (SD ±0.18) at final evaluation, and mean central macular thickness (CMT) improved from 461 µm (SD ±156) to 356 µm (SD ±110; net decrease: 105 µm, P=0.01). Mean logMAR VA for the RZB arm improved from 0.394 (SD ±0.31) to 0.269 (SD ±0.19) at final evaluation. Mean CMT improved from 421 µm (SD ±147) to 373 µm (SD ±129; net decrease: 48 µm, P=0.26).Conclusion: A subset of recalcitrant DME patients demonstrated significant CMT reduction and VA improvement after a single DEX injection. Keywords: aflibercept, bevacizumab, central macular thickness, macular edema, dexamethasone implant, diabetic macular edema, diabetic retinopathy, ranibizumab